(untitled) (Research, Society and Development, 2022)
Objective: to evaluate the indicators of good practices during the assistance to women in labor and birth. Method: quantitative, documentary, descriptive study with a cross-sectional design. Using documentary research in data collection, evaluating the indicators of good practices provided to pregnant women in labor from April to September 2019. The sample consists of 100% of births occurring during the study period regardless of it was a natural birth or a cesarean section. For data, analysis descriptive statistics are performed with absolute and relative frequency. Results: establishes that despite good practices, high amounts of interventions not recommended by the Ministry of Health prevail. Despite the recent inclusion of obstetric nurses in this service, it is perceptible the rate of good practices developed by these professionals was 100%. Conclusion: it has been noticed that there is a great challenge in the search for the transformation of assistance to women and newborns based on the good practices recommended by the Ministry of Health.